Tax collection in Roman Egypt: violence against taxpayers (Circe de clásicos y modernos, 2023)
The aim of our work is, then, to analyze the testimonies that show violence against taxpayers during tax collection in Roman Egypt in the 1st century AD. For this purpose, we will divide the study into two parts. In the first, we will investigate De Specialibus Legibus 2.92-95 and 3.159-163 of Philo of Alexandria in relation to the edicts of the prefects. Here we will examine especially the methods of torture along with the actions linked to government officials, such as the ἐκλογισταί. In the second, we will study the papyri and inscriptions that present requests or complaints from individuals affected by the violence of the collectors and their subordinates. This will allow us to review not only what were some of the events resulting from taxation in Roman Egypt, but also to what extent forced taxation affected the local economy.
Keywords: Tax collection; Roman Egypt; taxpayers; Philo; papyri; inscriptions